Conceptual reconstruction of energy concepts using the model of educational reconstruction in the German Didaktik tradition - Azlinah Ispal (2022)
This thesis sheds new light on how to prepare a physics lesson on energy concepts for upper secondary school students. Energy concepts are among the most important ideas in all of science. Similarly, the presence of energy as both a core concept and a cross-cutting concept will undoubtedly confuse students. This misunderstanding is caused by a number of identified factors, including differences in the definition of the word “energy” in the scientific world and in everyday conversation. Most textbook authors use complex terms that are commonly used by scientists but are difficult for students to understand. This problem is worsened when teachers are primarily dependent on the concepts restricted in the textbook and what is framed by the curriculum developer. Many teachers and physics educators believe that concepts for instruction must be “simpler” than the physics content itself in order for students to understand them after the “reduction” process from the original content structure. Unfortunately, this is also the reason why students struggle to understand energy concepts, particularly in physics. Thus, the researcher, who acted as a physics teacher in this study, has been investigating how students’ everyday-oriented energy conceptions can be reconstructed into physics-oriented conceptions. To achieve the study’s goal, the Model of Educational Reconstruction (MER) from the German Didaktik tradition was used as the framework of the research method. The research is based on Heidegger’s philosophical hermeneutics, in which physics is viewed as a “language of thought.” This inquiry’s data is derived from semi-structured interviews, written responses, teaching experiments, student written self-reflection, and researcher self-reflexivity. While qualitative content analysis and systematic metaphor analysis are used to triangulate and interpret the text, according to the findings of the study; students’ informal communication, culture, social media, and personal experiences influenced their language of thought, which profoundly shaped their understanding of the meaning of energy, which may or may not be correct. The most interesting finding was that most participants thought of potential energy as the “ability to do work,” but scientists thought of it in a different way. Students’ energy conceptions could be reconstructed and linked to scientific knowledge by interpreting their language of thought and meaning if they could only signify their conception as intelligible, plausible, and fruitful. This research on conceptual reconstruction of energy concepts contributes to the field of physics education knowledge, methodological issues, and has implications for the educational practises such as physics curriculum, instructional quality, assessment quality, and physics teacher quality. Thus, the MER from the German Didaktik tradition has the potential to be incorporated into our curriculum because this tradition emphasises the importance of conceptual clarification prior to beginning instruction, which has never been considered in our education.